2012
DOI: 10.1371/journal.pone.0032924
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Nasal and Bronchial Epithelial Cells Obtained from Patients with COPD

Abstract: For in vitro studies of airway pathophysiology, primary epithelial cells have many advantages over immortalised cell lines. Nasal epithelial cells are easier to obtain than bronchial epithelial cells and can be used as an alternative for in vitro studies. Our objective was to compare nasal and bronchial epithelial cells from subjects with COPD to establish if these cells respond similarly to pro-inflammatory stimuli. Cell cultures from paired nasal and bronchial brushings (21 subjects) were incubated with ciga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 44 publications
8
63
1
Order By: Relevance
“…Looking at the absolute values in the controls in our study, the bronchial epithelial cells produced the smallest amounts of IL-6 protein. This is consistent with previously published results [26,34]. Stimulation with TNF-α resulted in a greater increase in the IL-6 level in bronchial cells.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Looking at the absolute values in the controls in our study, the bronchial epithelial cells produced the smallest amounts of IL-6 protein. This is consistent with previously published results [26,34]. Stimulation with TNF-α resulted in a greater increase in the IL-6 level in bronchial cells.…”
Section: Discussionsupporting
confidence: 94%
“…In general, the reactivity of the nasal, bronchial and small airway epithelial cells was qualitatively similar, although in some cases substantial differences were observed. Similar differences in the reactivity of paired cultures of human nasal and bronchial epithelial cells were also observed by other authors [26,29]. We confirmed the earlier observations of many authors that CCL26 was the main eotaxin detected in cultures of human bronchial epithelial cells stimulated with IL-4 or IL-13 [30,31].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, the weight of evidence would support that CSE has predominantly pro-inflammatory [2,15,16] as opposed to immunosuppressive effects [17,18] on bronchial epithelial cells. Although there is evidence that nasal epithelial cells can act as a satisfactory substitute for bronchial epithelial cells for certain end-points, we have recently shown that bronchial epithelial cells respond differently to nasal epithelial cells to CSE treatment [19].…”
mentioning
confidence: 75%